Tradisi Ritual Manganjab di Nagori Sihaporas Kecamatan Pematang Sidamanik: Kajian Kearifan Lokal - Munthe, Alex Mujur Immanuel; Purba, Asriaty (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article is entitled "Manganjab Ritual Tradition in Nagori Sihaporas, Pamatang Sidamanik District, Simalungun Regency". This research aims to describe the stages in the Manganjab Tradition and describe the local wisdom values in the Manganjab Ritual Tradition in Nagori Sihaporas. The theory used is the local wisdom theory put forward by Robert Sibarani. The method used in this research is descriptive method. The results of the research show that the stages before the day of implementation are (1) Determining the Day, (2) Determining the Place of the Ritual, (3) and the stages of the day of the Manganjab Ritual. Local Wisdom in the Manganjab Ritual Tradition with 7 local wisdom values, namely: (1) Wisdom of Commitment, (2) Wisdom of Cultural Preservation and Creativity, (3) Wisdom of Mutual Cooperation, (4) Wisdom of Hard Work, (5) Wisdom of Gratitude , (6) Care for the Environment, (7) Politeness.